Characteristics of Publications on Occupational Stress: Contributions and Trends - Zhang, Yang; Huang, Lei; Wang, Yongwei; Lan, Yajia; Zhang, Yonggang (Frontiers in Public Health, 2021)
This study aimed to analyze the bibliometric characteristics of the publications on occupational stress and highlight key research topics and future trends. Web of Science Core Collection database was searched to collect publications on occupational stress, from inception to December 9, 2020. Two authors independently screened eligible literature and extracted the data. Bibliometric analyses were performed using VOSviewer 1.6.6 and R 3.6.3 software. Overall, 6,564 publications on occupational stress were included. “Stress,” with a total link strength of 1,252, appeared as the most co-occurrence keyword, followed by “occupational stress,” “job stress,” and “job satisfaction.” All studies were published between 1956 and 2020. Among them, 6,176 (94.35%) papers were written in English, and 4,706 (70.25%) were original articles. The top three Web of Science categories were “public environmental occupational health” (n = 1711), “psychology, applied” (n = 846), and “psychology, multidisciplinary” (n = 650). The 100 top-cited articles were mentioned a total of 36,145 times, with a median of 361, ranging from 174 to 5,574. USA was the most productive country, with 1,780 publications. The main partners of USA were England and China. Three themes of occupational stress research were identified: job satisfaction, burnout, and occupational stress-related health problems. This bibliometric analysis provides a comprehensive understanding of the trends and most influential contributions to the field of occupational stress, thus promoting ideas for future research.